Phenolic Metabolites from a Deep-Sea-Derived Fungus Aspergillus puniceus A2 and Their Nrf2-Dependent Anti-Inflammatory Effects - Jianlin He; Xin Wu; Shuhuan Huang; Juan Wang; Siwen Niu; Meixiang Chen; Gaiyun Zhang; Songyan Cai; Jingna Wu; Bihong Hong (Marine Drugs, 2022)
Four undescribed phenolic compounds, namely asperpropanols A–D (1–4), along with two known congeners 5 and 6, were isolated from Aspergillus puniceus A2, a deep-sea-derived fungus. The gross structures of the compounds were established by detailed analyses of the HRESIMS and NMR data, and their absolute configurations were resolved by modified Mosher’s method and calculations of ECD data. Compounds 1–6 were found to have excellent anti-inflammatory effect on lipopolysaccharide (LPS)-induced RAW264.7 cells at 20 μM, evidenced by the reduced nitric oxide (NO), tumor necrosis factor α, and interleukin 6 production. Among them, 5 and 6 showed inhibitory effects on NO production comparable with the positive control (BAY11-7083 at 10 μM). Additionally, the LPS-induced mRNA expressions of inducible nitric oxide synthase and cyclooxygenase-2 were also decreased. Interestingly, mRNA expression of nuclear factor erythroid 2–related factor 2 (Nrf2) was downregulated by LPS and recovered by 1–6, suggesting a vital role of Nrf2 in their effect. We further found that pharmacological inhibition of Nrf2 by ML385 largely abrogated the effects of 1–6 on RAW264.7 cells. Therefore, 1–6 may share a common anti-inflammatory mechanism via Nrf2 upregulation and activation.